Efektivitas Acceptance and Commitment Therapy (ACT) dalam Menangani Kecemasan dan Resiliensi Remaja: Sebuah Kajian Literatur - Muchammad Achsanul Hakim; Hendradi Styawan; Budi Purwoko; Bakhrudin All Habsy (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2026)
Acceptance and Commitment Therapy (ACT) is a contextual-based counseling approach that emphasizes acceptance of internal experiences and commitment to personal values as the foundation for behavioral change. This study aims to review previous research findings on the application of ACT among adolescents in both educational and non-educational contexts through a literature study approach. Data were retrieved from academic databases including Scopus, and Google Scholar covering publications from 2015 to 2025. A review of 10 studies showed that all reported ACT effectiveness, reaching a statistical significance of p < 0.05, including reduced anxiety, improved mental health, and increased psychological flexibility. ACT has been shown to be effective in a variety of service formats, including group counseling, online interventions, and short-term structured sessions. Practical implications for school guidance and counseling (BK) services include: (1) Integration of the ACT Approach in group counseling services by BK teachers, (2) Implementation of the ACT Counseling Approach in individual settings by BK teachers, (3) Development of an ACT counseling guidebook as a guide for school counselors, (4) As a suggestion in developing and training competencies related to the use of ACT counseling for teachers in an adaptive manner and according to student needs